The Influence Of Social Media On Consumer Intention To Buy Pt Dinamika Megatama Citra Pungging – Mojokerto - Fitrianah Nur; Rahayu; Syamsul Hidayat (International Journal of Management and Business Economics, 2023)
Social impact on consumer buying interest at PT Dinamika Megatama Citra. The method used in this study is a quantitative method with descriptive analysis based on primary data obtained directly through distributing questionnaires and secondary data obtained from related parties, interviews, books and journals, etc. This research was conducted by distributing questionnaires to respondents. The population in this study are employees and consumers of PT Dinamika Megatama Citra. While the sample used is 100 respondents with the criteria of being in the PT Dinamika Megatama Citra area which is active on social media until 2023. The sampling technique used is purposive sampling. The results of this study show that PT DINAMIKA MEGATAMA CITRA partially has a significant effect on consumer buying interest.